Factors Influencing Adoption of Improved Cultivars of Macadamia (Macadamia spp.) among Small-Scale Farmers in Embu County, Kenya - Njiru, Moses Muchangi; Mogaka, Hezron Ruzungu; Ndirangu, Samuel Njiir; Gichimu, Bernard Mukiri (Journal of Agricultural Extension, 2021)
The study investigated the factors influencing adoption of improved cultivars of macadamia (Macadamia spp.) among small-scale farmers in Embu County, Kenya. Data was collected from a sample of 384 small-scale farmers obtained through multistage sampling procedure in ten sub-locations. Binary Logit model was used to determine the effect of selected institutional and socio-economic factors on adoption of improved cultivars of macadamia. The results revealed that education level (wald=26.160), access to extension services (wald=6.246) and farm size (wald=4.271) had significant positive influence on adoption of improved cultivars of macadamia while age of the farmer (wald=5.235) and market distance (wald=5.519) had a negative influence on the same. There is need to encourage the youth to embrace macadamia farming and to develop smart marketing strategies to promote adoption of improved cultivars.
Artice
Keywords: Adoption; macadamia; small scale farmers